Mengembangkan E-Modul Berbantuan Augmented Reality Berbasis Kearifan Lokal Becak untuk Pembelajaran Fisika - Poppy Sari Dewi; Heru Kuswanto (Postgraduate, University of Mataram, 2023)
This study aims to reveal the feasibility of an augmented reality-assisted physics e-module based on the local wisdom of pedicabs in teaching. This study uses the 4-D development model (define, design, develop, and disseminate). The research data were obtained from the results of the product feasibility evaluation by material experts and media experts (two expert lecturers, three physics teachers, and two peer reviewers), as well as from the student response questionnaire. The result of the assessment by material and media experts shows the developed module is in the very good category. Assessment of student responses to the developed e-module on the circular motion material shows that in terms of the attractiveness aspect it is in a good category, and in terms of usability and operation aspects, it is in a good category. The developed augmented reality-assisted physics e-module based on the local wisdom of the pedicab is suitable for use in teaching circular motion materials